Carbon based multi-functional materials towards 3D system integration : application to thermal and interconnect management - Chow, W. L. (2013)
In order to meet the demands of increasing package density and miniaturization of devices without compromising performance, the most challenging issues to tackle are thermal and interconnect management. In this paper, we will first understand the interfacial transport between Si and Carbon for better system integration and discuss how novel carbon films can be used for thermal extraction. Second, we will show how carbon nanotubes can be used as interconnects using a flip chip approach as well as potential radio frequency applications.